Economic Value of Mangrove Forest Ecosystem in Unit XXXIII Kubu Raya Forest Management Unit - Handayani Handayani; Emi Roslinda; M. Sofwan Anwari (Jurnal Ilmu Kehutanan, 2023)
Mangrove forest ecosystems resources could serve as income sources for the surrounding communities. However, the total economic value of these resourceshas yet to be recognized, calculated, and considered in managing and conserving mangrove forest ecosystems. This research aimed to estimate the direct economic value (timber, charcoal, aquatic biota, processed products, honey, and Nypa roof), indirect economic values (abrasion prevention, carbon stock, oxygen production, intrusion barrier), and optional economic value (biodiversity) of mangrove forest ecosystems. This research used two assumptions to calculate the total economic values: with and without timber utilization activities for charcoal production in the Unit XXXIII Kubu Raya Forest Management Unit (FMU). The results indicated that the indirect economic value had the highest percentages compared to the direct and optional economic values in both assumptions.